2022
DOI: 10.3389/fphys.2021.794705
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Altered-Gravity on Bimanual Coordination: Retention and Transfer

Abstract: Many of the activities associated with spaceflight require individuals to coordinate actions between the limbs (e.g., controlling a rover, landing a spacecraft). However, research investigating the influence of gravity on bimanual coordination has been limited. The current experiment was designed to determine an individual’s ability to adapt to altered-gravity when performing a complex bimanual force coordination task, and to identify constraints that influence coordination dynamics in altered-gravity. A tilt … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 92 publications
2
3
0
Order By: Relevance
“…This would result in periods of shared neural drive with the initiation or release of the force command. This observation is consistent with the kinematic results of the current study ( Fig 3 ) as well as previous work demonstrating force distortions in the force and force-velocity time series for the non-dominant effector that was associated with the activation and release of force by the dominant effector [ 4 , 5 , 11 , 25 ]. In addition, research has indicated this influence continues to act on the non-dominant limb until the dominant limb achieves peak force velocity [ 4 ].…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…This would result in periods of shared neural drive with the initiation or release of the force command. This observation is consistent with the kinematic results of the current study ( Fig 3 ) as well as previous work demonstrating force distortions in the force and force-velocity time series for the non-dominant effector that was associated with the activation and release of force by the dominant effector [ 4 , 5 , 11 , 25 ]. In addition, research has indicated this influence continues to act on the non-dominant limb until the dominant limb achieves peak force velocity [ 4 ].…”
Section: Discussionsupporting
confidence: 93%
“…In a series of experiments, researchers demonstrated bimanual interference consistent with neural crosstalk during a 1:2 bimanual force task [4,5,11,[25][26][27][28]. The task required participants to produce two patterns of isometric force pulses with the dominant (right) effector for every pulse produced by the non-dominant (left) effector.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Unlike intrinsic coordination patterns such as in-phase and anti-phase, the generation of the 90° coordination pattern often necessitates extensive practice lasting for several consecutive days (5, 36). The current experiment aligns with previous findings by demonstrating that providing augmented visual feedback significantly reduces the typical practice time required for mastering complex coordination patterns (1, 3, 4, 13, 37, 38, 40, 42).…”
Section: Discussionsupporting
confidence: 90%
“…The cursor, representing the summed trajectory of two coordinated components, superimposed on the front of the Lissajous plot, is assumed to reduce incidental constraints (e.g., perceptual, cognitive, and environmental constraints) (41). This experimental arrangement facilitates a rapid improvement in performing the goal coordination pattern, providing an advantage for exploring behaviors and neural processes associated with complex bimanual coordination tasks (2, 4, 37, 39, 42).…”
Section: Introductionmentioning
confidence: 99%